Campaña de armonia familiar para favorecer el autoestimade los niños y niñas de primero de educación básica de la escuela Luis Fernando Vivero, de la Parroquia Juan Montalvo, cantón Latacunga, provincia de Cotopaxi en el año 2012-2013 - Morán Molina, Karen Patricia (2013)
This proposal is of vital importance, because the family harmony campaign can raise the self-esteem of children in the first year of basic education School “Luis. Fernando Vivero”, school where intra-family problems have been diagnosed affecting the emotional and educational fields of the infants, hence it is necessary to propose a family harmony campaign that can improve family ties through good communication between parents, teachers and students. This campaign has managed to raise awareness and emphasize what are the parents doing with their children. Also that the relationship between the school and the involved should stay unbreakable and should work together for the development and growth of the infants. This project has been performed in a open and very bias thus able to achieve the goals and objectives set, and see the positive change in the daily development of toddlers at home and in the school. The results are positive as behavior change in children has been remarkable and the transformation in parents goes in a evolutionary manner. This is the beginning of a change of behavior of both sides, but especially on the relationship between school and family and vice versa that goes in better ways. Furthermore it has come to see that the changes are positive and will be followed up to see improvement in all participants.